2004
DOI: 10.5194/angeo-22-3657-2004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating radiation belt losses though numerical modelling of precipitating fluxes

Abstract: Abstract. It has been suggested that whistler-induced electron precipitation (WEP) may be the most significant inner radiation belt loss process for some electron energy ranges. One area of uncertainty lies in identifying a typical estimate of the precipitating fluxes from the examples given in the literature to date. Here we aim to solve this difficulty through modelling satellite and ground-based observations of onset and decay of the precipitation and its effects in the ionosphere by examining WEP-produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 41 publications
(54 reference statements)
3
18
0
Order By: Relevance
“…The spatially varying mean WEP energy fluxes shown in Fig. 1 are combined with WEP energy spectra, in both cases calculated following the approach outlined in Rodger et al (2003Rodger et al ( , 2004b. The parameters of the WEP burst were selected by comparison with the calculations of Faraday Trimpi produced by WEP with a mean precipitation energy flux at L=2.23 of 2×10 −3 ergs cm −2 s −1 (Rodger et al, 2004b), specifically the "normal" Faraday Trimpi spectral conditions (Clilverd et al, 2004).…”
Section: Global Variation In Wep-driven Ionisation Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The spatially varying mean WEP energy fluxes shown in Fig. 1 are combined with WEP energy spectra, in both cases calculated following the approach outlined in Rodger et al (2003Rodger et al ( , 2004b. The parameters of the WEP burst were selected by comparison with the calculations of Faraday Trimpi produced by WEP with a mean precipitation energy flux at L=2.23 of 2×10 −3 ergs cm −2 s −1 (Rodger et al, 2004b), specifically the "normal" Faraday Trimpi spectral conditions (Clilverd et al, 2004).…”
Section: Global Variation In Wep-driven Ionisation Ratementioning
confidence: 99%
“…1 are combined with WEP energy spectra, in both cases calculated following the approach outlined in Rodger et al (2003Rodger et al ( , 2004b. The parameters of the WEP burst were selected by comparison with the calculations of Faraday Trimpi produced by WEP with a mean precipitation energy flux at L=2.23 of 2×10 −3 ergs cm −2 s −1 (Rodger et al, 2004b), specifically the "normal" Faraday Trimpi spectral conditions (Clilverd et al, 2004). Following the approach outlined in the Rodger et al (2003Rodger et al ( , 2004bRodger et al ( , 2005 studies, this starting point is used to derive global variations.…”
Section: Global Variation In Wep-driven Ionisation Ratementioning
confidence: 99%
“…Three of the four study days showed a high degree of consistency between the levels of lightning return stroke peak current required to produce any given perturbation scatter amplitude value, providing a link between the lightning currents and WEP energy flux (Clilverd et al, 2004). On the remaining day, the Trimpi signatures observed were 6-7 dB greater for a given lightning intensity than on the other study days, consistent with significantly harder radiation belt precipitation spectra (Rodger et al, 2004b), probably caused by post-geomagnetic storm acceleration processes of radiation belt electrons (Meredith et al, 2002).…”
Section: Introductionmentioning
confidence: 61%
“…We model the WEP burst following the approach outlined in Rodger et al ( , 2004b. The parameters of the WEP burst have been selected for comparison with the calculations of Faraday Trimpi produced by WEP with a mean precipitation energy flux at L=2.23 of 2×10 −3 ergs cm −2 s −1 (Rodger et al, 2004b), specifically the "normal" Faraday Trimpi spectral conditions (Clilverd et al, 2004).…”
Section: Modelling Of Dunedin Wep Trimpimentioning
confidence: 99%
See 1 more Smart Citation